Hubungan Antara Self Control Dengan Safety Driving Pada Pengemudi Bus Akap (Antar Kota Antar Provinsi) Di Kota Solo - Nugroho, Muhammad Rifa'i, Susatyo Yuwono ,S. Psi, M. Si., Psi (2017)
ABSTRACT Safety driving is a driving behavior to prevent traffic accident. Up to now, safety driving stiil a big problem in the communities. One of factor from safety driving is self control. The aims of research is to know the relationsof self control between safety driving on AKAP bus drivers. The hypothesis showed there was a positive relation self control between safety driving on akap bus drivers. The method used correlational study with quantitative approach which involving 150 AKAP bus driver's in Tirtonadi.Researcher used incidental sampling. Data collected by using both self control and safety driving scale. Meanwhile, the data was analyzed with correlation product moment and using SPSS (Statistical Product and Service Solution) 15.0 for Windows Program. The result obtained r amount 0,736; p=0,000 (p≤0,01), conducted there were positively significant correlation between self control to safety driving. It means, higher self control's people accordingly higher safety driving also, including the other hand. Based on analysis shows safety driving variable has empirical mean (RE) amount 77,54 and hypothetical mean (RH) amount 60 that means safety driving's respondent level is relatively high. The contribution of self control amount 54,2% to safety driving and left 45,8% from another variables of safety driving. Keywords: Self control, Safety driving, Bus drivers AKAP